A atuação de consórcio de exportação do segmento de moda praia e moda intima no Brasil: uma análise na perspectiva do marketing - Cruz, Breno de Paula Andrade (2007)
This dissertation tried to study qualitatively the performance of the exportation¿s consortiums in the segment of beach fashion in Brazil in the perspective of the marketing. Making use of the method of Grounded Theory, this study aimed to identify the categories that compose and make influence on the exporting performance of four consortiums in Brazil , based on the segment of beach fashion. This study becomes relevant because it classifies the categories found on the field research and exposes their relations. These categories have been characterized as big categories, intermediate categories and initial categories, having it¿s aim respectively: (a) to identify the characteristics found only on the studied consortiums; to identify (b) the promotional composition based on the (c) characteristics found in the segment of beach fashion. The study presents theoretical and managemental implications when shows two important categories that are relevant on the actuation of the exportation¿s consortiums on the external market, which are: knowledge of marketing in the external market and characteristics of the consortiums.